(untitled) (CIPEEX, 2024)
INTRODUCTION: ENVIRONMENTAL POLLUTION IS A GROWING PROBLEM WORLDWIDE AND CAN CAUSE A VARIETY OF HEALTH PROBLEMS, INCLUDING SKIN DAMAGE. EXPOSURE TO POLLUTION CAN LEAD TO PREMATURE SKIN AGING, SPOTS, WRINKLES AND OTHER CHANGES. IN THIS CONTEXT, THE USE OF TOPICAL RETINOIDS HAS BEEN STUDIED AS A STRATEGY TO PREVENT AND TREAT SKIN LESIONS CAUSED BY POLLUTION. OBJECTIVES: THE AIM OF THIS WORK IS TO CARRY OUT A LITERATURE REVIEW ON THE USE OF TOPICAL RETINOIDS IN THE PREVENTION OF SKIN LESIONS CAUSED BY ENVIRONMENTAL POLLUTION, FOCUSING ON THE MECHANISMS OF ACTION AND THE RESULTS OF CLINICAL STUDIES. METHODOLOGY: A SEARCH WAS CARRIED OUT IN THE GOOGLE SCHOLAR, PUBMED AND SCIELO DATABASES, USING THE DESCRIPTORS "TOPICAL RETINOIDS", "ENVIRONMENTAL POLLUTION", "SKIN LESIONS" AND "CLINICAL STUDIES". WE SELECTED ARTICLES PUBLISHED IN THE LAST 5 YEARS, IN PORTUGUESE, ENGLISH AND SPANISH, WHICH ADDRESSED THE USE OF TOPICAL RETINOIDS IN THE PREVENTION OF SKIN LESIONS CAUSED BY POLLUTION. LITERATURE REVIEW: RETINOIDS ARE SUBSTANCES DERIVED FROM VITAMIN A THAT HAVE ANTIOXIDANT AND ANTI-INFLAMMATORY PROPERTIES. THESE PROPERTIES CAN HELP PREVENT AND TREAT SKIN LESIONS CAUSED BY ENVIRONMENTAL POLLUTION. SEVERAL CLINICAL STUDIES HAVE INVESTIGATED THE USE OF THESE SUBSTANCES TOPICALLY TO PREVENT SKIN LESIONS CAUSED BY POLLUTION, INCLUDING THE USE OF TRETINOIN, ADAPALENE AND TAZAROTENE. THESE STUDIES HAVE SHOWN THAT THE USE OF THESE VITAMIN A DERIVATIVES CAN IMPROVE THE APPEARANCE OF THE SKIN, REDUCE SPOTS AND WRINKLES AND INCREASE SKIN ELASTICITY. IN ADDITION, TOPICAL RETINOIDS CAN HELP PROTECT THE SKIN AGAINST DAMAGE CAUSED BY FREE RADICALS AND OTHER OXIDIZING AGENTS PRESENT IN ENVIRONMENTAL POLLUTION. CONCLUSION: THE USE OF TOPICAL RETINOIDS TO PREVENT SKIN LESIONS CAUSED BY ENVIRONMENTAL POLLUTION IS A PROMISING AND SAFE STRATEGY. THEY CAN HELP PROTECT THE SKIN AGAINST DAMAGE CAUSED BY FREE RADICALS AND OTHER OXIDIZING AGENTS PRESENT IN ENVIRONMENTAL POLLUTION, AS WELL AS IMPROVING THE SKIN’S APPEARANCE. HEALTH PROFESSIONALS SHOULD BE PREPARED TO ADVISE PATIENTS ON THE USE OF TOPICAL RETINOIDS TO PREVENT SKIN LESIONS CAUSED BY ENVIRONMENTAL POLLUTION.